2007
DOI: 10.1136/thx.2006.067835
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory function in healthy young children using forced oscillations

Abstract: Background: Monitoring of respiratory function is important in the diagnosis and management of respiratory disease. The forced oscillation technique requires minimal patient cooperation and is ideal for the determination of respiratory function in young children. This study aimed to develop reference ranges and to document the repeatability in healthy young children using commercially available forced oscillation equipment. Methods: The forced oscillation technique, which uses a pseudo-random noise forcing sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
85
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 22 publications
(20 reference statements)
19
85
4
1
Order By: Relevance
“…Using the Australian equations 18 to calculate Z-scores for Italian children and comparing then with Z-scores calculated using the Italian equations from the present study showed minor differences for R rs10 (0.23, P ¼ 0.036), X rs8 (0.32, P ¼ 0.012), and X rs10 (0.65, P < 0.001). No significant differences were found for R rs6 (À0.02, P ¼ 0.82), R rs8 (0.10, P ¼ 0.43), and X rs6 (À0.02, P ¼ 0.68).…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…Using the Australian equations 18 to calculate Z-scores for Italian children and comparing then with Z-scores calculated using the Italian equations from the present study showed minor differences for R rs10 (0.23, P ¼ 0.036), X rs8 (0.32, P ¼ 0.012), and X rs10 (0.65, P < 0.001). No significant differences were found for R rs6 (À0.02, P ¼ 0.82), R rs8 (0.10, P ¼ 0.43), and X rs6 (À0.02, P ¼ 0.68).…”
mentioning
confidence: 87%
“…The Australian equation was compared to other equations previously published. 18 To date, no assessment of whether these data are applicable to other populations has been published.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The forced oscillation technique (FOT) is a promising lung function test that can measure the respiratory impedance of the lung in children as young as 2 years of age [17,21,22]. This technique is well suited to measurements in young children as it requires only tidal breathing and minimal cooperation from the child, and can be completed within 5-15 min.…”
Section: Introductionmentioning
confidence: 99%